THE POLICY OF GRANTING COMPENSATION AND APPARATUS PERFORMANCE IMPROVEMENT - Suharto Suharto; suwignyo Widagdo; Yuniorita Indah Handayani (MBA - Journal of Management and Business Aplication, 2019)
This study aims to determine the effect of compensation on employee performance, either partially or simultaneously. This research was conducted at Environment Agency of Bondowoso Regency with total sample of 100 employees. The analysis tool used is multiple linear regression with t test analysis tools and F test. The analysis process using SPSS statistical software. Hypothesis test results show that compensation consisting of basic salary, commission, incentive, structural allowance, overtime pay, social security, recognition and responsibility both partially and simultaneously affect the performance of employees. The contribution of variable compensation to employee performance is very dominant as evidenced by the coefficient of determinant 0.98%.